Robotic Exoskeleton Hand with Pneumatic Actuators - Pinto, Hugo Miguel Mantas Costa (2018)
With modern developments of smart portable devices and miniaturization of technologies, society has been provided with computerized assistance for almost every daily activity but the physical aspects have been frequently ne-glected. It is currently possible to make robots that process information thru neural networks, that identify and mimic facial expressions and that replace manual labour in assembly plants, getting ever closer to skills associated to human beings. In spite of these technological advances being kept close to they remain separate of humans, replacing or providing assistance with other pe-ripheral tasks, not generally adopting a direct physical symbiotic user assis-tance path. In this dissertation a robotic exoskeleton hand will be described that al-lows for human-machine bidirectional interaction making it possible to provide physical activities with the electromechanical assistance similarly. This system is designed to mimic the human hands functionalities and biomechanical struc-ture, as well sensing and controlling systems. A partial prototype was also built, using components easily acquired in the market, as a proof of concept.